Epidemiological and virological features of epidemic keratoconjunctivitis due to new human adenovirus type 54 in Japan. Issue 1 (8th June 2010) - Kaneko, Hisatoshi; Suzutani, Tatsuo; Aoki, Koki; Kitaichi, Nobuyoshi; Ishida, Susumu; Ishiko, Hiroaki; Ohashi, Tsutomu; Okamoto, Shigeki; Nakagawa, Hisashi; Hinokuma, Rikutaro; Asato, Yoshimori; Oniki, Shinobu; et al.
Abstract : Background/aims: New human adenovirus (HAdV)-54 causes epidemic keratoconjunctivitis (EKC) and is virologically close to and has occasionally been detected as HAdV-8. Taking HAdV-54 into account, we re-determined HAdV type in EKC samples to determine its epidemiology in Japan, and examined the virological features of HAdV-54. Methods: HAdV type was re-determined in 776 conjunctival swabs from Japan and 174 from six other countries, obtained between 2000 and 2009. Using 115 HAdV strains obtained before 1999, trends regarding HAdV-8 and HAdV-54 were also determined. In addition, immunochromatography (IC) kit features, DNA copy numbers and viral isolation of HAdV-54 in samples were evaluated. Results: Recently, HAdV-37 and HAdV-54 have been the major causative types of EKC in Japan. HAdV-54 has been isolated each year since 1995, whereas HAdV-8 has become less common since 1997, although it remains the most common cause of EKC in the six other countries investigated where HAdV-54 is yet to be detected. HAdV-54 is comparable to other EKC-related HAdV types in terms of IC kit sensitivity and DNA copy numbers, although HAdV-54 grows more slowly on viral isolation. Conclusions: EKC due to HAdV-54 can result in epidemics; therefore, it should be accurately diagnosed and monitored as an emerging infection worldwide.